STUDY ON BREAST-FEEDING PRACTICESOF POOR AND NONPOOR HOUSEHOLD - Mudjajanto, Eddy S.; Khomsan, Ali; Sukandar, Dadang; Anwar, Faisal; Riyadi, Hadi (PERSATUAN AHLI GIZI INDONESIA, 2006)
Breast-feeding is a natural way to feed babies. A good breastfeeding practice is important for a continued growth, health, and nutrients for babies and young children. Therefore, the period of exclusive breast-feeding is one of important health problems in the community. This research used a control group design. The control group is nonpoor household. The collected data from the two groups (poor and nonpoor) and from the two locations, Bogor and Indramayu, (highland and coastal) were compared. Sample was drawn as random. Sample size of poor households are 513 in both location, while nonpoor households are 238. Total sample size are 751 households. The data collected through questionnaires. The results of the studies conducted in Bogor and Indramayu show that most mothers either from poor or nonpoor households do not breastfeed their babies, and they have problems with their excessive breast milk and continuously dripping breast milk. The results of the study reveal that almost all mothers have got the experience of breast-feeding their last babies, either those of poor households or those of nonpoor ones in both Bogor and Indramayu. Most mothers of poor households both in Bogor and Indramayu do not generally understand about exclusive breast-feeding, with the figures reaching 95.6% and 97.7% respectively. The figures for the breast-feeding period of between 12 and 23 months were 27.4% in Bogor, and 30% in Indramayu.Key words: breast-feeding, households, breast milk, mothers, babies